Визначення регламенту зміни коефіцієнта втрат - Кузнецов, Валерій Геннадійович; Босий, Д. О.; Кирилюк, Тетяна Ігорівна (НТУ "ХПІ", 2013)
На основі методу Монте-Карло, встановлено закон розподілу коефіцієнта втрат. Визначені ступені впливу кожного з факторів на втрати електроенергії в контактній мережі. Надані рекомендації що до періодичності зміни коефіцієнта втрат.

The author established a distribution law of energy losses coefficient and provided recommendations for its regulations. It's obtained a regression for determining the energy losses for railway sections of determinate and alternating currents that can improve the accuracy of the losses definition.
Keywords: втрати електроенергії; лічильник втрат; метод Монте-Карло; коефіцієнт кореляції; налаштування лічильника; energy losses; Monte Carlo method; correlation coefficient; rules change; meter settings